Arithmetic Average Density Fusion-Part IV: Distributed Heterogeneous Fusion of RFS and LRFS Filters via Variational Approximation - Li, Tiancheng; Liang, Haozhe; Li, Guchong; Garcia Herrero, Jesus; Pan, Quan (IEEE transactions on signal processing, 2025)
This paper is the fourth part of a series of papers on the arithmetic average (AA) density fusion approach and its application for target tracking. In this paper, we address the intricate challenge of distributed heterogeneous multisensor multitarget tracking, where each inter-connected sensor operates a probability hypothesis density (PHD) filter, a multiple Bernoulli (MB) filter or a labeled MB (LMB) filter and they cooperate with each other via information fusion. Our recent work has proven that the existing linear fusion of these filters is all exactly built on averaging their respective unlabeled/labeled PHDs. Based on this finding, two PHD-AA fusion approaches are proposed via variational minimization of the upper bound of the Kullback-Leibler divergence between the local and multi-filter averaged PHDs subject to cardinality consensus based on the Gaussian mixture implementation, enabling heterogeneous filter cooperation. One focuses solely on fitting the weights of the local Gaussian components (L-GCs), while the other simultaneously fits all the parameters of the L-GCs at each sensor, both seeking average consensus on the unlabeled PHD, irrespective of the specific posterior form of the local filters. For the distributed peer-to-peer communication, both the classic consensus and flooding paradigms have been investigated. Simulations have demonstrated the effectiveness and flexibility of the proposed approaches in both homogeneous and heterogeneous scenarios.